Iron star - Estleman, Loren D. (Forge, Tor Publishing Group, 2024)
"From his youth as a revolutionist to his time as a Deputy U.S. Marshal, aging lawman Iron St. John has become a larger-than-life figure-and in the process, the man has disappeared behind the myth. During his brief, unsuccessful political career, St. John published his memoirs-a sanitized version of his adventures to appeal to the masses. A generation later, the clouded truth of this giant of the Old West has been all but lost. Now, Buck Jones, a pioneering film star, is vying for a cinematic story that will launch his career to incredible heights. He approaches Emmet Rawlings, a retired Pinkerton detective, to set the record of St. John's life straight once and for all. Twenty years ago, Rawlings accompanied St. John on his final manhunt, and in desperate need for the funding a successful book promises, he dives deep into St. John's past-and his own buried memories-to tell the truth about this part-time hero."--